Understand teachers’ apparent resistance to reforms: case of secondary school’s «cantonal assessments» in Waldensian physical education - Grandchamp, Annabelle Virginie; Quin, Grégory; Méard, Jacques (Swiss Journal of Educational Research, 2020)
A recent reform of the summative assessment in physical education (PE) was launched in 2015 in the canton of Vaud. This reform, effective in schools from the start of the 2016-2017 school year, has received a mixed reception from PE teachers. The purpose is to understand the nature of professional reactions in order to go further the mere «impression of dissatisfaction» and to relate these reactions to assessment details, dominant view of PE and institutional logics. Results reveal PE teachers’ reluctance because of an instability perception and some institutional tensions, but also because of the contested usefulness of the last reform and its assessments.